2019
DOI: 10.3390/foods8120691
|View full text |Cite
|
Sign up to set email alerts
|

Using Content Analysis to Characterise the Sensory Typicity and Quality Judgements of Australian Cabernet Sauvignon Wines

Abstract: Understanding the sensory attributes that explain the typicity of Australian Cabernet Sauvignon wines is essential for increasing value and growth of Australia’s reputation as a fine wine producer. Content analysis of 2598 web-based wine reviews from well-known wine writers, including tasting notes and scores, was used to gather information about the regional profiles of Australian Cabernet Sauvignon wines and to create selection criteria for further wine studies. In addition, a wine expert panel evaluated 84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Some samples in Cluster 2 indicated that 'minty' flavour was an important characteristic, although in general not much difference was seen between the samples (Figure 1A). A 'minty' character has been reported previously for Coonawarra Cabernet-Sauvignon wines, which might indicate this as a dominant trait for the Coonawarra region (Robinson et al, 2011;Souza Gonzaga et al, 2019;Souza Gonzaga et al, 2020). Characters described as 'minty' and 'eucalyptus' in Cabernet-Sauvignon wines have been associated with the presence of eucalyptol (i.e., 1,8-cineole) and hydroxycitronellol, and although 'eucalyptus' aroma and flavour were not statistically significant (α = 0.1) in the present work (Supplementary data, Table S3), studies have shown that they might be interchangeable and indistinguishable by a sensory panel (Capone et al, 2012;Robinson et al, 2011;Souza Gonzaga et al, 2020).…”
Section: Rata Sensory Profiling and Clustering Of Winesmentioning
confidence: 56%
See 1 more Smart Citation
“…Some samples in Cluster 2 indicated that 'minty' flavour was an important characteristic, although in general not much difference was seen between the samples (Figure 1A). A 'minty' character has been reported previously for Coonawarra Cabernet-Sauvignon wines, which might indicate this as a dominant trait for the Coonawarra region (Robinson et al, 2011;Souza Gonzaga et al, 2019;Souza Gonzaga et al, 2020). Characters described as 'minty' and 'eucalyptus' in Cabernet-Sauvignon wines have been associated with the presence of eucalyptol (i.e., 1,8-cineole) and hydroxycitronellol, and although 'eucalyptus' aroma and flavour were not statistically significant (α = 0.1) in the present work (Supplementary data, Table S3), studies have shown that they might be interchangeable and indistinguishable by a sensory panel (Capone et al, 2012;Robinson et al, 2011;Souza Gonzaga et al, 2020).…”
Section: Rata Sensory Profiling and Clustering Of Winesmentioning
confidence: 56%
“…Cluster 5 was especially related to 'cherry cola' and 'vanilla/chocolate' flavours (Figure 1B), as opposed to the savoury profile found for Cluster 1 (Figure 1A). Sensory profiles have similarly been used in the past for regional classification of Australian Cabernet-Sauvignon wines (Souza Gonzaga et al, 2019;Souza Gonzaga et al, 2020) and Australian Shiraz and Chardonnay wines (Kustos et al, 2020). Those studies with commercial wines reported that some distinctive sensory traits can be more important and more associated with a specific wine-producing region, with the current work on unreleased wines also indicating the existence of perceived differences within a GI according to Figure 1.…”
Section: Rata Sensory Profiling and Clustering Of Winesmentioning
confidence: 99%
“…In this case, descriptions provided by the expert panel were analysed through a text mining tool so that sensory characteristics could be assessed (Souza Gonzaga et al 2019). These results were compared with a large collection of webbased wine reviews by well-known wine writers, also analysed with the text mining methodology, thereby revealing some agreement between the two cohorts for the sensory attributes that were considered important for the evaluated GIs (Souza Gonzaga et al 2019). Leriche et al (2020) have recently proposed a methodology to assess the sensory typicity of wines coming from a region controlled by PDO regulation.…”
Section: Approaches To Measure Wine Sensory Typicitymentioning
confidence: 99%
“…In another study utilising the expertise of industry professionals, Souza Gonzaga et al (2019) used a free vocabulary description approach with the aim of elucidating the sensory typicity of Australian Cabernet Sauvignon wines. In this case, descriptions provided by the expert panel were analysed through a text mining tool so that sensory characteristics could be assessed (Souza Gonzaga et al 2019).…”
Section: Approaches To Measure Wine Sensory Typicitymentioning
confidence: 99%
See 1 more Smart Citation